The Role of Thrombelastography in Multiple Trauma - Victor Jeger; Heinz Zimmermann; Aristomenis K. Exadaktylos (Emergency Medicine International)
Hemorrhage and traumatic coagulopathyis are major causes of early death in multiply injured patients. Thrombelastography (TEG) seems to be a fast and accurate coagulation test in trauma care. We suggest that multiply injured trauma patients would benefit the most from an early assessment of coagulation by TEG, mainly RapidTEG, to detect an acute traumatic coagulopathy and especially primary fibrinolysis, which is related with high mortality. This review gives an overview on TEG and its clinical applications.